Heterogeneity in farmers production decisions and its impact on soil nutrient use: results and implications from northern Nigeria - Berkhout, Ezra D.; Schipper, R.A.; Keulen, H. van; Coulibaly, O. (Elsevier, 2011)
Sustainable use (in terms of nutrients) of soil resources by farmers in Sub-Saharan Africa is constrained by institutions and markets. This paper explores the case of northern Nigeria, by using a combination of multi-attribute utility theory and bio-economic modelling. This approach allowed us to identify heterogeneity in production strategies and to quantify its effect on the use of soil nutrient resources.